2016
DOI: 10.1080/10903127.2016.1233311
|View full text |Cite
|
Sign up to set email alerts
|

Ability of the Physiologic Criteria of the Field Triage Guidelines to Identify Children Who Need the Resources of a Trauma Center

Abstract: The Physiologic Criteria are a moderate predictor of trauma center need for children. Missing or inaccurate vital signs may be limiting the predictive value of the Physiologic Criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 13 publications
0
40
1
Order By: Relevance
“…With regard to the use in children, the tool integrates adaption of physiological and amnestic criteria. However, in a recent retrospective study of trauma triage in children in the USA, the physiologic criteria showed only a moderate predictive capacity to appropriately determine a trauma center need for children [24]. Specific pediatric trauma scores facilitate the decision process for pediatric trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the use in children, the tool integrates adaption of physiological and amnestic criteria. However, in a recent retrospective study of trauma triage in children in the USA, the physiologic criteria showed only a moderate predictive capacity to appropriately determine a trauma center need for children [24]. Specific pediatric trauma scores facilitate the decision process for pediatric trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…It could be suggested that an incomplete triage could jeopardise patient safety and thus omit significant abnormal vital signs. However, previous studies have shown that VS are only moderate predictors when assessing children in need of a trauma centre [ 43 ] and, furthermore, that there is a correlation between the degree of acuity level and the number of VS that were registered [ 44 ]. Even though measuring VS in the EMS care of injured and sick children has been emphasised to reduce under-triage [ 45 , 46 ], implementing VS in all the patients in the MTS for paediatrics did not improve performance [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent retrospective study of trauma triage in children in the US, the physiologic criteria showed only a moderate predictive capacity to appropriately determine a trauma center need for children. (23) Speci c pediatric trauma scores facilitate the decision process for pediatric trauma patients. For example, the pediatric trauma score was developed to predict injury severity and mortality after pediatric major trauma.…”
Section: Discussionmentioning
confidence: 99%